Pharmacoeconomic rationale for switching patients with rheumatic diseases from original biologic disease-modifying antirheumatic drugs to biosimilars in context of the Russian healthcare system - A. Yu Kulikov; V. G. Serpik; A. M. Lila (Современная ревматология)
Objective: to analyze the pharmacoeconomic efficiency of biosimilars in context of national healthcare system.Material and methods. Based on the developed interactive pharmacoeconomic model, we made an analysis of the impact on the budget of treatment with biologic disease-modifying antirheumatic drugs (bDMARDs) and targeted synthetic disease-modifying antirheumatic drugs (tsDMARDs) in patients with rheumatoid arthritis (RA), spondyloarthritis (SpA), patients with psoriatic arthritis (PsA) were analyzed separately, within the framework of the study a cost-effectiveness analysis of bDMARD and tsDMARD therapy was performed to determine the preferred alternative in RA.Results and discussion. The performed pharmacoeconomic analysis confirmed the research hypothesis on the economic feasibility of transferring patients with rheumatic diseases (RA, PsA and SpA) receiving original bDMARDs to biosimilars in the context of Russian healthcare system. According to the cost analysis, biosimilars, except for infliximab, are characterized by comparatively less cost of a treatment course than the original drugs. The results of the budget impact analysis and cost analysis prove the economic feasibility of switching patients from original bDMARDs to biosimilars. At the same time, the parameters of the current and planned distributions entered in the calculations of the analysis of the impact on the budget, indicate the need of the professional community and patients for a wider use of innovative original bDMARDs that are under patent protection. At the same time, in the context of budgetary constraints, switching to biosimilars remains perhaps the only available strategy for increasing the coverage of patients with innovative drugs. It has been established that the etanercept biosimilar (ETC) Erelzy® has the lowest cost-effectiveness value. At the same time, ETC is characterized by the highest clinical efficiency, which makes it possible to determine the specified ETC biosimilar as strictly preferable from the point of view of the cost-effectiveness analysis.Conclusion. It can be assumed that in the absence of medical contraindications, switching of RA patients to ETC from other bDMARDs will be accompanied by better control of the disease, and the presence of biosimilars of ETCs, including the drug Erelzi®, which are among bDMARDs with the lowest cost of treatment course, will save funds, that can be rerouted to extend the coverage of patients with bDMARDs or increase the proportion of innovative bDMARDs.